Massification of higher education in Malaysia: managing institutional equity and diversity / Muhammad Muftahu, Devisakti Annmali and Hu Xiaoling - Muftahu, Muhammad; Annmali, Devisakti; Hu, Xiaoling (Universiti Teknologi MARA, 2023)
In the last few decades, the world has witnessed a rapid increase in the number of students in higher education institutions, leading to the massification of higher education. This paper investigates how the massification of higher education has affected institutional diversity and equity in Malaysia. Semi-structured interviews were conducted with top management and mid-level managerial staff in one of the top research universities in Malaysia. The findings showed that the massification of higher education in Malaysia has implications for students’ equity and diversity. The analysis illustrates that this higher education institution in Malaysia has taken steps to keep up with massification, but barriers still exist that hinder students in terms of access to higher education. Although there was diversity among the students in the institution, access to higher education for underprivileged students’ needs special attention due to the inequality of their position in society. This study contributes to meaningful ways of looking at the massification of higher education in relation to diversity and equity from an institutional perspective.